2018
DOI: 10.22146/aci.40853
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Risk Factors of Coronary Heart Disease in Diagnostic Value of Treadmill Score for Detecting Complexity of Coronary Arterial Lesions

Abstract: Background: Coronary heart disease (CHD) is still the leading cause of death in the world. There are various risk factors for atherosclerosis leading to CHD. Duke Treadmill Score (DTS) is known to demonstrate prognostic stratification and has a diagnostic value in predicting the number of coronary arteries involved in patient populations with ischemic heart disease. However, DTS does not describe the role of risk factors for coronary heart disease to the complexity of coronary artery lesions. This study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…(11) A limitation, however, that did not affect these studies is that DTS, does not describe the role of modifiable cardiovascular risk factors for complexity of coronary artery disease. (6,12) Our research found no data…”
Section: Angiogram Done Cross-tabulationmentioning
confidence: 73%
See 1 more Smart Citation
“…(11) A limitation, however, that did not affect these studies is that DTS, does not describe the role of modifiable cardiovascular risk factors for complexity of coronary artery disease. (6,12) Our research found no data…”
Section: Angiogram Done Cross-tabulationmentioning
confidence: 73%
“…Despite our finding, it has previously been demonstrated that DTS is useful in stratifying patient risk categories. (1,11,12) A noted limitation of DTS is the exclusion of modifiable cardiovascular risk factors. This is significant because the pre-test assessment for CAD is based on cardiovascular risk factors (demographic and medical comorbidities) and not on DTS alone.…”
Section: Discussionmentioning
confidence: 99%
“…CAD is one of the leading causes of death in this era. 7 Duke Treadmill score is an important predictor of CAD 8,9 as well as the prognosis 10 . Zaman M et al 11 This finding reinforces the regional as well as ethnic differences in the trends of CAD and its risk factors.…”
Section: Discussionmentioning
confidence: 99%